Renal clearance of heparin-binding protein and elimination during renal replacement therapy: Studies in ICU patients and healthy volunteers. - Line Samuelsson; Jonas Tydén; Heiko Herwald; Magnus Hultin; Jakob Walldén; Ingrid Steinvall; Folke Sjöberg; Joakim Johansson (PLoS ONE, 2019)
Background Heparin-binding protein (HBP) is released by neutrophils upon activation, and elevated plasma levels are seen in inflammatory states like sepsis, shock, cardiac arrest, and burns. However, little is known about the elimination of HBP. We wanted to study renal clearance of HBP in healthy individuals and in burn patients in intensive care units (ICUs). We also wished to examine the levels of HBP in the effluent of renal replacement circuits in ICU patients undergoing continuous renal replacement therapy (CRRT). Methods We measured plasma and urine levels of HBP and urine flow rate in 8 healthy individuals and 20 patients in a burn ICU. In 32 patients on CRRT, we measured levels of HBP in plasma and in the effluent of the CRRT circuit. Results Renal clearance of HBP (median (IQR) ml/min) was 0.19 (0.08-0.33) in healthy individuals and 0.30 (0.01-1.04) in burn ICU patients. In ICU patients with cystatin C levels exceeding 1.44 mg/l, clearance was 0.45 (0.15-2.81), and in patients with cystatin C below 1.44 mg/l clearance was lower 0.28 (0.14-0.55) (p = 0.04). Starting CRRT did not significantly alter plasma levels of HBP (p = 0.14), and the median HBP level in the effluent on CRRT was 9.1 ng/ml (IQR 7.8-14.4 ng/ml). Conclusion In healthy individuals and critically ill burn patients, renal clearance of HBP is low. It is increased when renal function is impaired. Starting CRRT in critically ill patients does not alter plasma levels of HBP significantly, but HBP can be found in the effluent. It seems unlikely that impaired kidney function needs to be considered when interpreting concentrations of HBP in previous studies. Starting CRRT does not appear to be an effective way of reducing HBP concentrations.